Congenital heart disease in aircrew. (13th November 2018) - Nicol, Edward D; Manen, Olivier; Guettler, Norbert; Bron, Dennis; Davenport, Eddie D; Syburra, Thomas; Gray, Gary; d'Arcy, Joanna; Rienks, Rienk
Abstract : This article focuses i on the broad aviation medicine considerations that are required to optimally manage aircrew ii with suspected or confirmed congenital heart disease (both pilots and non-pilot aviation professionals). It presents expert consensus opinion and associated recommendations and is part of a series of expert consensus documents covering all aspects of aviation cardiology. This expert opinion was born out of a 3 year collaborative working group between international military aviation cardiologists and aviation medicine specialists, as part of a North Atlantic Treaty Organization (NATO) led initiative to address the occupational ramifications of cardiovascular disease in aircrew (HFM-251) many of whom also work with and advise civil aviation authorities.